AKTUALISASI NILAI-NILAI OLAHRAGA SEBAGAI UPAYA MEMBANGUN KARAKTER BANGSA - Yustinus Sukarmin (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: Actualization of Sports Values as an Attempt to Build Nation Character. Honesty, caring, politeness, loyalty, discipline, and responsibility are some good values that should be the foundations the nation’s life. At present, however, they are rarely found in daily life. Deceit, carelessness, rudeness, hypocrisy, and negligence are more dominant in the country. In sports, some good values, such as devotion, fairness, discipline, cooperation, and hard work can be actualized as an attempt to rebuild the nation character. They must be actualized in various aspects of life through leaders’ exemplary deeds in the family, school, society, and country.